Pursuing the Magic of Words in the Twentieth-Century’s Croatian and Serbian Literature - Czapik-Lityńska, Barbara (Poznańskie Studia Slawistyczne, 2013)
The essay titled „Pursuing the Magic of Words in the Twentieth-Century’s Croatian and Serbian Literature” discusses transformations of the awareness of the avant-garde and postmodernism from the perspective of its relation to magic thinking. The essay advances a vision of poetic language and the main figures of the avant-garde’s imagination, especially the aesthetic conceptualizations of the messianic archetype. The avant-garde thinking about the world of unity (of the world-man-language) is utopian and not infrequently magic-esoteric. Postmodernism deconstructs symbolic language; it does not share the avant-garde’s belief in the existential and creative power of imagination and the word. The virtual culture of postmodernism reduces the value of the language sign and the referential function of language; it disenchants the conceits of the magic word.